2013
DOI: 10.1002/jgrd.50247
|View full text |Cite
|
Sign up to set email alerts
|

The radar tropopause above Svalbard 2008–2012: Characteristics at various timescales

Abstract: [1] Determinations of the tropopause altitude over Adventdalen, Svalbard (78 N, 16 E) have been assembled for the period 2008-2012. These reveal characteristics at various timescales: interannual, seasonal, and stochastic. First, it is established that the inclusion of considerably more data does not alter earlier findings of good temporal agreement with radiosonde measurements, that the radar tropopause is located at a fairly constant altitude above the meteorological tropopause, and that the seasonal vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…If such effects were capable of, for example, triggering the springtime breakdown of the polar vortex, associated horizontal transport of stratospheric ozone would contribute to determination of the tropopause altitude (e.g. Hall, 2013) and, again, gravity wave propagation. Overall change in the stratosphere is proposed as the origin of the observed strengthening of the Brewer-Dobson circulation during the last 35 years at least (Fu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…If such effects were capable of, for example, triggering the springtime breakdown of the polar vortex, associated horizontal transport of stratospheric ozone would contribute to determination of the tropopause altitude (e.g. Hall, 2013) and, again, gravity wave propagation. Overall change in the stratosphere is proposed as the origin of the observed strengthening of the Brewer-Dobson circulation during the last 35 years at least (Fu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…If such effects were capable of, for example, triggering the springtime breakdown of the polar vortex, associated horizontal transport of stratospheric ozone would contribute to determination of the tropopause altitude (e.g. Hall, 2013) and, again, gravity wave propagation. Overall change in the stratosphere is proposed as the origin of the observed strengthening of the Brewer-Dobson circulation during the last 35 years at least (Fu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The generation of turbulence and its height distribution vary with season and similarly affect the turbopause altitude (e.g. Hall et al, 1997). Turbulence is somewhat distributed through the high-latitude win-2300 C. M. Hall et al: Change in turbopause altitude at 52 and 70 • N ter mesosphere, whereas in summer the gravity waves "save their energy" more until reaching the "steep beach" (a visualisation attributable to M. E. McIntyre, personal communication, 1988) of the summer mesopause near 85 km.…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat exhaustive comparisons have been made between the radar results which will be presented here and the tropopause determinations from radiosonde soundings nearby (Ny‐Ålesund, 79°N, 12°E), showing a high degree of agreement in temporal behavior and that the altitude difference between the two determinations is almost invariant—1.8 ± 0.3 km—with a slight seasonal variation [ Hall et al . ; Hall , ] contained within the standard deviation. It has been demonstrated that it is viable to convert between radar and cold‐point tropopause altitudes at least for the SOUSY radar and radiosonde measurements currently available on Svalbard.…”
Section: Introductionmentioning
confidence: 99%
“…At both intra‐annual and interannual scales, the agreement in temporal variation between the climatology and the 78°N, 16°E observations is good. Although not a topic of this study, there is a suggestion of convergence of the observations on the climatology, indicative of a systematic increase in tropopause height over the 5 years of measurements [ Hall , ]. Subsequently in this study, underlying 1 h resolution values will be used, and the term “tropopause” will be used to refer to the radar (height of peak echo) tropopause hereafter.…”
Section: Introductionmentioning
confidence: 99%